2018
DOI: 10.1108/bij-05-2016-0065
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable evaluation and selection of potential third-party logistics (3PL) providers

Abstract: Purpose The purpose of this paper is to efficiently assist the decision makers in evaluating and selecting the most appropriate third-party logistics (3PL) provider from environmental sustainability perspective using a two-phase model based on data envelopment analysis (DEA) and analytic network process (ANP). Design/methodology/approach The study uses an integrated approach of DEA and ANP as an evaluation and selection methodology to select an efficient and requisite 3PL. The integrated model is a sound tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 68 publications
1
37
0
2
Order By: Relevance
“…Para la evaluación de los 3PL desde la perspectiva de la sustentabilidad ambiental, Raut et al (2018) implementan una metodología MCDM en dos fases: DEA y ANP. Los autores proponen un método integrado para la toma de decisiones en el proceso de selección y evaluación de 3PL basado en el desempeño desde una perspectiva de sustentabilidad ambiental.…”
Section: Evaluación Y Selección De 3plunclassified
See 1 more Smart Citation
“…Para la evaluación de los 3PL desde la perspectiva de la sustentabilidad ambiental, Raut et al (2018) implementan una metodología MCDM en dos fases: DEA y ANP. Los autores proponen un método integrado para la toma de decisiones en el proceso de selección y evaluación de 3PL basado en el desempeño desde una perspectiva de sustentabilidad ambiental.…”
Section: Evaluación Y Selección De 3plunclassified
“…Enfoques y métodos para la evaluación y selección de 3PL Datos (DEA)Raut et al (2018),Marchet et al (2017),Haldar et al (2017),Momeni et al (2015),Falsini et al (2012),Zhang et al (2006) Proceso Analítico en Red (ANP)Raut et al (2018),Çelebi et al (2010) Técnica Difusa para Orden de Preferencia por Similitud con Solución Ideal (TOPSIS)Bianchini(2018), Haldar et al (2017), Ilgin (2017), Yayla et al (2015) Toma de decisiones interactiva y de criterios múltiples (TODIM) Kumar Sen et al (2017) Método de Organización de Clasificación de Preferencias para Evaluaciones Enriquecidas (PROMETHEE) Kumar Sen et al (2017), Wang et al (2015), Chen et al (2010) Importancia a través de la Correlación entre Criterios (CRITIC) Ghorabaee et al (2017) Evaluación del Producto de Suma Agregada Ponderada (WASPAS) Laboratorio de Prueba y Evaluación en Entornos Grises para la Toma de (DEMATEL) Govindan et al (2016) Números Difusos con Valores de Intervalo (IVFNs) Sahu et al (2015) Despliegue de la Función de Calidad (QFD) Perçin and Min (2013) Proceso Analítico de Jerarquía (AHP) Bianchini (2018), Hwang et al (2016), Falsini et al (2012), Soh (2010), Zhang et al (2006) Proceso Analítico de Jerarquía Difuso (AHP Difuso) Ilgin (2017), Jung (2017), Ramírez-Flores et al(2017) conjuntos difusos Li et al (2012), Soh(2010), Liu and Wang (2009), Işiklar et al (2007) Razonamiento Basado en Casos (CBR) Işiklar et al (2007) Razonamiento Basado en Reglas (RBR)…”
unclassified
“…A new term related to logistics services is Fourth-Party Logistics (4PL) which considers companies that provide novel, integrated, or customized services using the resources of other companies. Raut, Kharat, Kamble, and Kumar [25] used Data Envelopment Analysis (DEA) and Analytical Network Process (ANP) to evaluate 3PL companies. The result revealed that 3PL causes better transportation, inventory, and warehouse management.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, the implementation of the statistical approaches requires a collection of measurable quantitative data from the beginning of the study, while artificial intelligence methods are used to model knowledge rather than data. The strength of MCDM methods is to present themselves as effective alternatives to methods of classic optimization such as mathematical programming, based on the definition of a single function, often expressed in economic (monetary) terms and which reflects the consideration of several criteria, often immeasurable (Pourjavad & Shirouyehzad, 2011;Raut et al, 2018). More generally, as noted by Fenies (2011), decision support in the logistics context is now at the crossroads, as far as any modeling approach must simultaneously integrate algorithmic and systemic complexities of the problem posed, here LSP selection.…”
Section: Locationmentioning
confidence: 99%